2016
DOI: 10.1063/1.4940749
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced surface transfer doping of diamond by V2O5 with improved thermal stability

Abstract: Surface transfer doping of hydrogen-terminated diamond has been achieved utilising V2O5 as a surface electron accepting material. Contact between the oxide and diamond surface promotes the transfer of electrons from the diamond into the V2O5 as revealed by the synchrotron-based high resolution photoemission spectroscopy. Electrical characterization by Hall measurement performed before and after V2O5 deposition shows an increase in hole carrier concentration in the diamond from 3.0x1012 to 1.8x1013cm2 at room t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 30 publications
5
41
1
Order By: Relevance
“…[32][33][34][35][36] Along with the extreme semiconducting properties such as ultrawide bandgap of 5.5 eV, high thermal conductivity, and high breakdown field, diamond electronic devices provide the attractive route to develop the next-generation electronic devices able to operate under high-power, high-frequency, and high-temperature conditions. The surface density of the 2DHG on H-terminated diamond is as high as 10 13 cm −2 and can reach 10 14 cm −2 when properly selecting the surface molecular or oxides.…”
Section: Resultsmentioning
confidence: 99%
“…[32][33][34][35][36] Along with the extreme semiconducting properties such as ultrawide bandgap of 5.5 eV, high thermal conductivity, and high breakdown field, diamond electronic devices provide the attractive route to develop the next-generation electronic devices able to operate under high-power, high-frequency, and high-temperature conditions. The surface density of the 2DHG on H-terminated diamond is as high as 10 13 cm −2 and can reach 10 14 cm −2 when properly selecting the surface molecular or oxides.…”
Section: Resultsmentioning
confidence: 99%
“…Kasu et al found that the NO 2 (≈5 ppb) in air could induce a p‐type conductivity on H‐terminated diamond, and the NO 2 , NO, O 3 , and SO 2 gases form the surface holes. In addition, some solid‐state oxides with high positive affinity can be surface electron acceptor material, such as MoO 3 , V 2 O 5 , Nb 2 O 5 , and WO 3 . However, assuming that the surface negative charge is responsible for the formation of hole accumulation would be sufficient for our calculation.…”
Section: Parameters Used In the Calculationmentioning
confidence: 99%
“…[36]. It may be worth while to note here that the Fermi-level position for airborne SC H-terminated diamond was initially reported to be 0.7 eV below E V [39,40] and that this appeared to be contradictory to the later reports [29,37,38].…”
Section: Discussionmentioning
confidence: 75%
“…Another concern in Ref [36] is that C 1s peak binding energy appeared at 283.74 eV for H-terminated diamond (100). This should be about 284.0 eV for airborne surface-conductive H-terminated diamond as found in this study and in other recent studies [37,38]. The binding-energy calibration might be in error in…”
Section: Discussionmentioning
confidence: 78%